Cache Node Placement Scheme Considering Maximum Traffic in Content-Centric Networks - Pavarangkoon, Praphan; Nakajima, Shohei; Kitsuwan, Nattapong (My University, 2023)
This paper proposes a cache node placement scheme considering the maximum traffic in content-centric networks (CCNs). The cache node placement problem is considered to satisfy the user's requirement in CCNs. Traffic utilization is one of the most common requirements. Reduced traffic allows more additional traffic on links. In this paper, a scheme to minimize the maximum traffic and the number of hops is proposed. The mathematical model for the cache node placement problem is formulated. The dynamic routing is considered in this model. Numerical result shows that the proposed scheme outperforms the conventional scheme. It suggests that the proposed scheme provides reference values to support the implementation of heuristic algorithms for the cache node placement problem.
Keywords: Content-centric networking; maximum traffic; optimization